Impact of training and professional development on health management and leadership competence: A mixed methods systematic review. Issue 4 (28th June 2019) - Ayeleke, Reuben Olugbenga; North, Nicola Henri; Dunham, Annette; Wallis, Katharine Ann
Abstract : Purpose: Training to improve health management and leadership competence is recommended. However, there is limited evidence showing the impact of training on competence. The purpose of this paper is to evaluate the evidence for the impact of training and professional development on health management and leadership competence. Design/methodology/approach: A systematic review was conducted using a mixed-methods design. Studies using qualitative, quantitative or mixed-methods design were included. The following electronic databases were searched to October 2018: CENTRAL, CINAHL, EMBASE, ERIC, NEDLINE and PsycINFO. Study eligibility and methodological quality were assessed independently by two review authors. Data from qualitative studies were synthesised using thematic analysis. For quantitative studies, odds ratio (OR) or mean difference (MD) and 95% confidence interval (CI) were calculated for each intervention. Where appropriate, qualitative and quantitative data were integrated into a single synthesis using Bayesian methods. Findings: In total, 19 studies were identified for inclusion in the review. Training and professional development interventions using flexible, multiple training techniques tailored to organisational contexts can improve individual competence and performance. Such training is typified by a leadership development programme. There was insufficient evidence to determine the effects of interventions on organisational performance. Originality/value: This is the first systematic review evaluating the impact of training and professional development interventions on health management and leadership competence.